Employee Well-Being as a Strategy to Improve Performance and Retention of Outsourced Employees at PT SSI - Dewi, Dinda Amelia; Uus Mohammad Darul Fadli; Ery Rosmawati (Research in Management of Technology and Business, 2026)
The outsourcing industry poses distinct challenges for organizations in sustaining employee well-being, performance, and retention among contract-based workers. This study examines the role of employee well-being in supporting performance and encouraging retention among outsourced employees at PT SSI. Data were obtained through in-depth interviews with five informants and analyzed using a thematic analysis approach. The results show that employee well-being is generally perceived as favorable, particularly due to positive work relationships, health-related support, and the maintenance of work–life balance. However, these conditions tend to deteriorate during periods of high workload. Employee performance is also regarded as relatively strong, supported by training initiatives, oversight of SOP implementation, regular performance evaluations, and organizational recognition. In terms of retention, key influencing factors include the fulfillment of employee rights and wages, contract security, and opportunities for career development, although uncertainty regarding employment status remains a significant concern. Overall, the findings emphasize the importance of employee well-being in enhancing performance and reinforcing employees’ decisions to remain with the organization, while offering practical insights for organizations in managing workload and developing outsourced personnel.